Genes Essential to Iron Transport in the Cyanobacterium Synechocystis sp. Strain PCC 6803 - Katoh, Hirokazu (American Society for Microbiology, 2001)
Genes encoding polypeptides of an ATP binding cassette (ABC)-type ferric iron transporter that plays a major role in iron acquisition in Synechocystis sp. strain PCC 6803 were identified. These genes are slr1295, slr0513, slr0327, and recently reported sll1878 (Katoh et al., J. Bacteriol. 182:6523–6524, 2000) and were designated futA1, futA2, futB, and futC, respectively, for their involvement in ferric iron uptake. Inactivation of these genes individually or futA1 and futA2 together greatly reduced the activity of ferric iron uptake in cells grown in complete medium or iron-deprived medium. All the fut genes are expressed in cells grown in complete medium, and expression was enhanced by iron starvation. The futA1 and futA2 genes appear to encode periplasmic proteins that play a redundant role in iron binding. The deduced products of futB and futC genes contain nucleotide-binding motifs and belong to the ABC transporter family of inner-membrane-bound and membrane-associated proteins, respectively. These results and sequence similarities among the four genes suggest that the Fut system is related to the Sfu/Fbp family of iron transporters. Inactivation of slr1392, a homologue of feoB in Escherichia coli, greatly reduced the activity of ferrous iron transport. This system is induced by intracellular low iron concentrations that are achieved in cells exposed to iron-free medium or in the fut-less mutants grown in complete medium.